Examining the rural-urban divide in predisposing, enabling, and need factors of unsafe abortion in India using Andersen's behavioral model - Margubur Rahaman; Puja Das; Pradip Chouhan; Kailash Chandra Das; Avijit Roy; Nanigopal Kapasia (BMC, 2022)
Abstract Background The prevalence of unsafe abortions significantly varies with geography; therefore, more research is needed to understand the rural-urban differences in unsafe abortion practices in India. The present study aims to explore the rural-urban differences in predisposing, enabling, and need factors of unsafe abortion in India. Methods The present study used the fourth round of the National Family Health Survey (2015-16) and included the women aged 15-49 who terminated pregnancies by induced abortion during the 5 years prior to the survey (N = 9113) as the study sample. Descriptive statistics, bivariate chi-square significance test and multivariate logistic regression model were used to accomplish the study objectives. Results The findings revealed that almost one-third of pregnancies were terminated through unsafe measures with sharp rural-urban contrast. The likelihood of unsafe abortions increases with decreasing women's age and spousal level of education. Younger women in urban settings were more vulnerable to unsafe abortion practices. In rural settings, women with an uneducated spouse are more likely to have unsafe abortions (OR: 1.92). Poor households were more likely to undergo unsafe abortions, which were more common in rural settings (OR: 1.26). The unmet need for family planning was revealed to be a significant need factor for unsafe abortion, particularly in rural settings. Conclusion Although abortion is legal, India's high estimated frequency of unsafe abortions reveals a serious public health issue. Due to socio-economic vulnerability, unmet family planning needs, and a lack of awareness, significant numbers of women still practice unsafe abortions in India.